Cellular recruitment and cytokine generation in a rat model of allergic lung inflammation are differentially modulated by progesterone and estradiol - Oliveira, Ana Paula Ligeiro de; Domingos, Helori Vanni; Cavriani, Gabriela; Damazo, Amilcar Sabino [UNESP]; Franco, Adriana Lino dos Santos; Oliani, Sonia Maria [UNESP]; Oliveira-Filho, Ricardo Martins; Vargaftig, Bernardo Boris; Lima, Wothan Tavares de (Amer Physiological Soc, 2007)
We evaluated the role of estradiol and progesterone in allergic lung inflammation. Rats were ovariectomized (Ovx) and, 7 days later, were sensitized with ovalbumin (OA) and challenged after 2 wk with inhaled OA; experiments were performed 1 day thereafter. Ovx-allergic rats showed reduced cell recruitment into the bronchoalveolar lavage (BAL) fluid relative to sham-Ovx allergic rats, as was observed in intact allergic rats treated with ICI-182,780. Estradiol increased the number of cells in the BAL of Ovx-allergic rats, whereas progesterone induced an additional reduction. Cells of BAL and bone marrow (BM) of Ovx-allergic rats released elevated amounts of IL-10 and reduced IL-1 beta and TNF-alpha. BM cells of Ovx-allergic rats released increased amounts of IL-10 and lower amounts of IL-4. Estradiol treatment of Ovx-allergic rats decreased the release of IL-10 but increased that of IL-4 by BM cells. Estradiol also caused an increased release of IL-1 beta and TNF-alpha by BAL cells. Progesterone significantly increased the release of IL-10, IL-1 beta, and TNF-alpha by BAL cells and augmented that of IL-4 by BM cells. Degranulation of bronchial mast cells from Ovx rats was reduced after in vitro challenge, an effect reverted by estradiol but not by progesterone. We suggest that the serum estradiol-to-progesterone ratio might drive cellular recruitment, modulating the pulmonary allergy and profile of release of anti-inflammatory or inflammatory cytokines. The existence of such dual hormonal effects suggests that the hormone therapy of asthmatic postmenopausal women and of those suffering of premenstrual asthma should take into account the possibility of worsening the pulmonary conditions.
Keywords: Asthma; Eosinophils